Sexual satisfaction and associated individual factors among midlife and older people in Ile-Ife, Southwest Nigeria: implications for sexual and reproductive health - Omotosho, Rhoda Oluwatofunmi; Solanke, Bola Lukman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Studies in Nigeria have rarely documented the prevalence and associated factors of sexual satisfaction among the midlife and older persons as a special group of underserved population in the country. This study investigates the prevalence and individual associated factors of sexual satisfaction among the midlife and older people in Ile-Ife, Southwest Nigeria. Methods: A sample size of 404 was analysed in the study. The outcome variable was sexual satisfaction. The explanatory variables are sets of individual and relational characteristics. Data were analysed using Stata 14. Bivariable and multivariable binary logistic regression models were estimated. Results: Findings reveal 42.0% level of sexual satisfaction. Higher educational attainment (AOR=0.864, p<0.01; 95% CI: 0.841-0.886), longer length of marriage (AOR=0.931, p<0.01; 95% CI: 0.912-0.950), remarriage (AOR=0.536, p<0.01; 95% CI: 0.387-0.742), economic inactivity (AOR=0.456, p<0.01; 95% CI: 0.322-0.646) reduces the odds of sexual satisfaction while absence of serious health challenges (AOR=2.742, p<0.01; 95% CI: 1.594-4.716) and spousal high wealth level (AOR=1.038, p<0.01; 95% CI: 1.017-1.059) increase the odds of sexual satisfaction. Conclusions: Individual characteristics of midlife and older men and women are significantly associated with their sexual satisfaction. These characteristics should be targeted in a special programme focusing on midlife and older persons in Nigeria.